Enriched sewage sludge from anaerobic pre-treatment in spurring valorization potential of black soldier fly larvae - Raksasat, R. (Academic Press Inc., 2022)
The valorization of sewage sludge by black soldier fly larvae (BSFL) has gained attentions for sewage sludge management since the sludge can be reduced securely as well as larval biomass can be used for biorefineries application. Nevertheless, the BSFL growth was impeded while assimilating nutrition from sewage sludge due to the presence of extracellular polymeric substances (EPS) that had entrapped the essential nutrients inside. Accordingly, the pre-treatment of sewage sludge via anaerobic digestion at different pH was employed in this work to rupture the EPS structure and release more nutrients for larval growth. The results showed that larvae fed with raw sewage sludge had attained the lowest final larval weight (2.05 ± 0.38 mg/larva) as opposed to batches fed with pre-treated sewage sludges. This was because the soluble carbohydrate (more than 6.81 ± 1.31 mg of glucose/g sewage sludge) in EPS was released after anaerobic pre-treatment, facilitating larval assimilation for growth. Furthermore, it was observed that further increasing of pH for sewage sludge pre-treatment had led to lower final larval weight gained due to the inhibitory effect stemming from ammonia production at higher pH. The anaerobic pre-treatment of sewage sludge being executed at pH 3 for 8 days had achieved the highest final larval weight at 7.34 ± 0.97 mg/larva. The still low quality of sewage sludges after the pre-treatment also offered benefit, where high sewage sludge reduction and waste reduction index were recorded due to the necessity of BSFL to consume more sewage sludge in compensating the nutrients destitution in sludge. Lastly, the possibility of predicting final larval weight was successfully materialized via a statistical model derived from the multiple linear regression method. The derived model incorporated the interactive parameters of anaerobic pre-treated pH and durations at various combinations could predict the final larval weight. © 2022 Elsevier Inc.